A Longitudinal Study of the Factor VII Rise during Pregnancy - Wright, D.; Poller, L.; Thomson, J. M.; Sidebotham, A.; Hirst, C. F.; Hirsch, P. (Thrombosis and Haemostasis, 1998)
A longitudinal study of 21 pregnant women has been undertaken using a variety of factor VII assays, including factor VIIa, to investigate the increase of factor VIIc. All assays demonstrated significant rises (p <0.001), most marked for factor VIIa (82%) and factor VIIc rabbit (81%). Smaller rises were seen for factor VIIc bovine (50%) and VII antigen (40%). Three indirect measures of activity state, factor VIIc rabbit:antigen, bovine:antigen and bovine:rabbit, provided conflicting data. Factor VIIa:antigen showed a significant increase of 36% (p <0.001). Within individual pregnancies the change in factor VIIc rabbit and antigen correlated with maternal weight gain (p <0.05). Two activity state measures, bovine:rabbit and bovine:antigen, showed negative correlation with birthweight. The increases in both zymogen and in activity state appear to contribute to the factor VIIc rise. The extent of this rise appears to be influenced by maternal weight gain. Increased factor VII activation is associated with reduced foetal growth.